Kinetic Studies on the Oxidation of Orange-II by Cr(VI) In Absence and Presence of Micelle forming Surfactants - Sarada, N.C.; Ajit Kumar Reddy, I. (Asian Journal of Chemistry, 2010)
Kinetic studies on the oxidation of Orange-II by Cr(VI) in acid medium revealed that the reaction is first order with respect to each of the reactants. Rate is also found to be proportional to hydrogen ion concentration. A mechanism consistent with the results for the cleavage of –N═N– by the oxidant has been proposed. 0.02M concentration of Brij-35 inhibited the rate of oxidation by 10 times. Micelles of sodium dodecyl sulfate (SDS) have little effect on the rate. Micelles of cetyltrimethyl ammonium bromide (CTAB) so strongly inhibited the rate, that no appreciable change in the substrate concentration is detected in 2 hrs. Influence of surfactants on the rate has been discussed on the basis of the reaction mechanism and the interactions between the substrate and micelles. Analysis of Brij-35 effect on the basis of a model proposed to explain the micellar effects gave a value of 3.89 x 10–4s–1 for rate constant in micellar phase and 2.28 x 103M–1 for micelle-substrate binding constant. Activation parameters for the reaction in absence and presence of surfactants have been compared.